SOSIALISASI TERAPI HORTIKULTURA UNTUK MENINGKATKAN SELF EFFICACY PADA PASIEN DENGAN GANGGUAN JIWA AKIBAT DEPRESI DI WILAYAH KERJA UPTD PUSKESMAS PLERED PURWAKARTA - Yuli Erlina; Grace, Grace; Mila Mega (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Depression is a type of emotional disorder that has a psychological component: feelings of sadness, hopelessness, and unhappiness, as well as a somatic component: anorexia, constipation, clammy (cold) skin, decreased blood pressure and pulse. Patients with mental disorders due to depression can interfere with a person's self-confidence to solve problems or decrease self-efficacy, in increasing the value of self-efficacy, one of which is by providing horticultural therapy. The purpose of this case study was to analyze the value of self-efficacy in patients after horticultural therapy at the UPTD Puskesmas Plered Purwakarta. This type of research is descriptive using a case study approach. The subject in this study was one patient with mental disorders due to depression with criteria that had started to be cooperative, the contents of the conversation can be understood clearly, do not experience visual disturbances, like gardening, and have never received horticultural therapy before. Self efficacy analysis was carried out descriptively and measured based on the GSES (General Self Efficacy Scale). The results of the analysis are categorized into disagree, somewhat agree, almost agree, strongly agree. Categories are determined based on the minimum criteria of 30 points, higher scores indicate higher self-efficacy. The results of the study showed that there was an increase in the value of self-efficacy after giving horticultural therapy